Problems of Hadith Mediatization on Reels Video, Youtube Short and Tiktok - Ahmad Nadlif (CONTEMPLATE: Jurnal Ilmiah Studi Keislaman, 2024)
In the current era of industrial revolution 4.0, it appears that the process of transmitting hadith has experienced a shift. Hadith, which was originally transmitted using a strict process using the tahammul wal ada' method, now seems to have been denied by social media which has become a free space for disseminating hadith. Hadith texts that appear on social media, certainly have interesting problematic gaps to study. This article aims to show the various patterns of hadith transmission that are spread in Reels, YouTube Short and TikTok. Using a library research methodology, this type of qualitative research study also refers to the mediatization concept approach as an analytical design. The results of this research found at least three models of hadith transmission spread across on new media, namely first, videos that only mention hadith and have background sound, this content tends to be textual and provides instant understanding; second, interpretation of hadith accompanied by videos or images as a form of contextualization; and third, snippets of lectures from figures who quote hadith. The three transmission models each have different impacts. The lecture fragment model is a form of transmission that is quite compatible, because it provides the text of the hadith and its explanation comprehensively. Meanwhile, video models that only provide translations of hadiths and background music are the weakest transmission of hadiths, because they can create confusion in understanding hadiths and there are concerns that there will be a bias towards opinions and even ideologies towards certain communities.